Marketing Communication of Selected Conservative and Liberal Parties in Slovak Region before Elections - Jánošová, Denisa; Bundzíková, Renáta (Political Preferences, 2020)
Through a democratically set system of state functioning, political parties are given space for their establishment and subsequent functioning. Nowadays, registering new parties is not an issue in Slovakia, but another issue arises - most political parties cannot attract voters, and as a result they lose general sympathy and also necessary votes in elections. For a political party to become known to its voters, it needs to address and subsequently implement techniques of political marketing. Reaching and gaining voters is essential for a political party to continue to exist. By using marketing communication in its election campaign, a political party can succeed more than the one that has not used them. Therefore to adequately address its voters, a political party has to know their social, cultural, economic as well as religious background. The political party must also pay attention to the creation of an election program that appeals to voters. However, a political party should choose such proper communication channels through which it will be able to attract its supporters. The presented paper deals with the issue of using / not using marketing communication before the parliamentary elections in 2020 in selected Slovak conservatively and liberally oriented political parties in the Trenčín region. The authors present their findings on the basis of the analysis of marketing communication tools, as well as formuate research questions that helped them meet the research goal, in particular, whether selected political parties used/did not use specific marketing communication tools in their election campaign in 2020.